Measuring performance in the portuguese banking industry with a Fourier regression model - Barros, Carlos Pestana (2022)
This article analyses the determinants of banks’ profitability in the Portuguese banking sector during the period 1990 to 2005. The study extends the established literature on modelling the banks’ performance by applying a Fourier approximation in order to detect for possible nonlinearities between the profitability variables and the explanatory variables. In so doing, we verify that the introduction of the Fourier coefficients in the analysis quite improved the quality of the adjustments, the need to accept the existence of nonlinear relationships among the variables involved in the study thus becoming evident. The results of this article suggest that the best performing banks in the Portuguese banking sector are those which have endeavoured to improve their capital and labour productivity, those which have maintained a high dimension and, finally, those which have been able to reinforce their capital structure.